X-LINKED CONGENITAL ADRENAL HYPOPLASIA: A CASE REPORT - Ramakrishnan, Banumathy; Selveindran, Nalini; Yong, Janet Yeow Hua (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Adrenal hypoplasia congenita is a rare disease. It is characterized by primary adrenal insufficiency and/or hypogonadotropic hypogonadism (HH). Approximately 60% of affected males experience acute infantile onset while the remaining 40% have childhood onset. NR0B1/DAX1 plays a pivotal role in the development and function of the adrenal and reproductive axes. Loss of NR0B1/DAX1’s inhibitory property due to NR0B1 mutations was demonstrated to be responsible for the pathology of X-linked adrenal hypoplasia congenita (AHC) and hypogonadotropic hypogonadism (HH). CASE We present a 15-year-old male who was initially referred to us at 1 year old when he presented with adrenal crisis. He was treated empirically with Hydrocortisone, Fludrocortisone, and sodium supplementation which was weaned off after infancy. Synacthen test showed poor adrenal response with peak cortisol of <30 nmol/L, low 17OHP with ACTH levels of 9.7 pmol/L, suggestive of primary adrenal Insufficiency. During the course of follow-up he was noted to have delayed puberty. Physical examination showed no dysmorphism, normal blood pressure, prepubertal Tanner Staging with AH1PH1 and testicular volume of 2 mls bilaterally. Stretched penile length was 5 cm with width of 1.5 cm (<10th centile). LHRH stimulation test confirmed HH, after which IM Testosterone was started. Genetic testing revealed a pathogenic mutation in the NR0B1 gene (NP_000466.2:p. Ser175ValfsTer14) Hemizygous. CONCLUSION In conclusion, we report a patient with adrenal hypoplasia congenital with novel mutation of NR0B1/ DAX-1 gene. Early diagnosis is important for long-term treatment in terms of endocrine and reproductive function and genetic counseling; the possibility of a NROB1/ DAX- 1 mutation must be considered in male patients with adrenal insufficiency.